Divine Sovereignty and The Global Climate Change Debate. - Wilson, Holly L. (Essays in Philosophy, 2010)
An essay is presented on debate between global climate change and divine sovereignty. It relates the article "Hacked E-Mail Is New Fodder for Climate Dispute," by Andrew Revkin which indicates that American difficulty on climate debate is a matter between science and business. It also explores the viewpoint of Roman Catholic on global climate change and the call of the U.S. Conference of Catholic Bishops Inc. for responsibility by the ones who primarily contributed to global warming.